A Novel Hybrid Image Encryption Algorithm Based on Data Compression and Chaotic Key Planning Algorithms - Burhan, Yucel; Artuger, Firat; Ozkaynak, Fatih (Ieee, 2019)
In this study, a hybrid image encryption algorithm which provides data compression and encryption requirements is proposed. Both JPEG and fractal compression algorithms can be used in the data compression process of the proposed new algorithm. In the encryption process, a chaotic key planning algorithm has been used. Chaotic systems are used as an entropy source. This approach, based on the one time pad principle, is unconditionally secure because it uses different secret keys in each encryption process. Successful analysis results show that the proposed new method can be used in many practical applications in the field of information security.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: chaos; cryptology; image encryption; data compression